2020
DOI: 10.12659/msm.929347
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Apolipoprotein C1 (APOC1) in Clear Cell Renal Cell Carcinoma and Its Prognostic Significance

Abstract: Background The aims of this study included 3 aspects: 1) assessing the expression of Apolipoprotein C1 (APOC1) in clear cell renal cell carcinoma (ccRCC) and normal groups; 2) evaluating the prognostic significance of APOC1 expression in the overall survival (OS) of ccRCC patients; and 3) exploring APOC1-related signaling pathways. Material/Methods The APOC1 expression value and clinical data of ccRCC patients were obtained from the cBioPortal database. We then evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Some previous studies have also supported this hypothesis and have reported the prognostic value of individual genes in a variety of tumors. For example, APOC1 is closely related to poor prognosis in ccRCC patients, as well as age, clinical stage, and pathological grade ( Xiao and Xu, 2021 ). C1QA and C1QB might be potential prognostic factors and indices of tumor microenvironment remodeling in osteosarcoma ( Chen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have also supported this hypothesis and have reported the prognostic value of individual genes in a variety of tumors. For example, APOC1 is closely related to poor prognosis in ccRCC patients, as well as age, clinical stage, and pathological grade ( Xiao and Xu, 2021 ). C1QA and C1QB might be potential prognostic factors and indices of tumor microenvironment remodeling in osteosarcoma ( Chen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mapped gene APOC1 (apolipoprotein C1) is a protein-coding gene engaged in the inhibition of cholesteryl ester transfer protein (CETP). A study showed that APOC1 was highly expressed in clear cell renal cell carcinoma ( 47 ), and a variant of APOC1 called T45S led to elevated rates of T2D ( 48 ). The second strongest SNP was rs4565329 (mapped gene: CENPW , P meta = 7.64×10 -14 ).…”
Section: Resultsmentioning
confidence: 99%
“…HERV and solitary LTR elements can cause several human diseases such as azoospermia, multiple sclerosis, schizophrenia, diabetes, and cancer ( Conrad et al, 1997 ; Kamp et al, 2000 ; Karlsson et al, 2001 ; Kim et al, 1999a ; 1999b ; Li et al, 2020 ; Patzke et al, 2002 ; Perron et al, 1997 ; Xiao and Xu, 2021 ). Apolipoprotein C1 ( APOC1 ) appears to be an independent prognostic factor in patients with clear cell renal cell carcinoma (ccRCC).…”
Section: Herv and Solitary Ltr Elements Are Implicated In Various Hum...mentioning
confidence: 99%
“…Apolipoprotein C1 ( APOC1 ) appears to be an independent prognostic factor in patients with clear cell renal cell carcinoma (ccRCC). APOC1 could be a potential therapeutic target for ccRCC as it regulates cell growth and metastasis pathways ( Xiao and Xu, 2021 ). APOC1 promotes metastasis of ccRCC cells by activating STAT3 .…”
Section: Herv and Solitary Ltr Elements Are Implicated In Various Hum...mentioning
confidence: 99%